PENGEMBANGAN EKONOMI KREATIF OLAHAN JAMBU METE DI KAMPUNG SARMAYAM INDAH - Aldisa Arifudin; Nurwijayanti Nurwijayanti (Musamus Devotion Journal, 2020)
The implementation of this creative economy development service is aimed at mothers in Sarmayam Indah Village. The community service activity begins with socialization by providing knowledge about the creative economy (understanding, characteristics, types, and development in Indonesia), processing procedures, materials, equipment and benefits of cashew nuts, and also about the importance of sanitation application and hygienic in the process of cashew processing. Then the cashew nut processing training was conducted through demonstration and demonstration methods. The training begins with transferring knowledge to participants about good raw materials for various cashew preparations, the types of products that will be practiced in activities, as well as an explanation of how to produce good and right. There was also a two-way discussion so that participants could understand more about the material presented. The success of this community service activity can be seen from the ease of receiving new knowledge and wanting to implement it. Because mothers in Sarmayam Indah Village have good potential as cashew nut processing businesses to play a role in advancing Sarmayam Indah Village